Using machine learning tools and methods for finding similar products according to user - Pirko, Andrii; Boretska, Iryna (Комп’ютерне моделювання та інформаційні технології, 2023)
The main methods of applying machine learning to search for similar products according to user preferences is described. A method is developed to create a model that can be used to create information systems for searching for relevant products. The results of the study can be used to implement an information system for searching for goods in any field of e-commerce.